An Analysis of Distance Learning Success for History Subject in the Covid-19 Pandemic Era - Wulan Nurjanah; Akhmad Arif Musadad; Hieronymus Purwanta (Indonesian Academy of Social and Religious Research (IASRR), 2021)
The Covid-19 pandemic has impacted all fields of life, including education. Indonesia through the Ministry of Education, Culture, Research, and Technology has issued a policy called learning from home. The implementation of the policy is carried out with the help of technology and the internet. This article provides an overview of the implementation of learning from home policy. Researchers aim to find out the success of distance learning for history subject during the Covid-19 pandemic. The research was conducted on history distance learning, which was performed in XI IPA 5 class of SMA Negeri 2 Pandeglang. This study used a qualitative descriptive approach with a case study approach. The results show that distance learning implemented at SMA Negeri 2 Pandeglang is considerably successful because it has fulfilled five factors in the success of distance learning, namely institutional management, learning environment, learning design, supporting services, and learning evaluation.